Financial Literacy and Investment Behavior among Customers of Commercial Banks in Kathmandu Valley: Evidence from Logistic Regression Analysis - Shrestha, Ranu Maiya; Adhikari, Reena; Adhikari, Samyog (Academia Journal of Research and Innovation, 2026)
Financial literacy is a decisive factor in the personal financial health and investment choices, and the effect of financial literacy on the personal accumulation of wealth and the economic development rate is immense. This paper looks into the financial literacy rates and investment behavioral patterns of customers of commercial banks in Kathmandu Valley with the help of a comprehensive primary survey research. A cross sectional study on 600 bank client individuals in 15 commercial bank branches was conducted with the use of structured questionnaires and financial literacy tests to analyze the level of knowledge, investment preference as well as behavior across various demographic groups. The study used analytical examination of literacy measures and investment decisions and qualitative evaluation of the decision making and obstacles towards accessing financial opportunities. Findings showed that the financial literacy levels were moderate and averaged at 62 percent on standardized tests with great differences in education levels (university graduates: 74% vs. secondary education: 48%), age groups (younger customers: 66% vs. female customers: 58%), and by gender (male customers: 66% vs. female customers: 58%). The analysis of investment behavior showed that 78 or percent of the customers used basic savings products and only 34 and 28 percent are involved in equity investment and mutual fund respectively. Investment diversification (r = 0.67, p < 0.001) and risk-adjusted returns (r = 0.52, p < 0.01) had a strong positive correlation with financial literacy. Greater literacy rates were correlated with more advanced investment planning, reduced use of informal advice as well as improved long-term financial planning. The results are useful to the financial institutions and policymakers who aim at improving financial inclusion and development of the investment market by implementing specific literacy programs and improving product design.